Pawon as a main education chamber of multicultural values among Tenggerese society - Nurdin, Kurniawan Dindasari; Yusuf, Achmad (Postgraduate Program of State Islamic University (UIN) Salatiga Jl. Lingkar Salatiga Km. 02 Salatiga, Indonesia https://pps.uinsalatiga.ac.id/, 2022)
Family education is very strategic because it is the first and foremost education carried out continuously in large portions. This study analyzed the pawon as a place for children’s education regarding how it was carried out and what values were taught. The author focused on discussing the values of multicultural Islamic education. It was conducted using a qualitative method, so the data was qualitative, collected through interviews, observation, and documentation. In the Tenggerese society, the pawon is a fireplace and can be interpreted as a kitchen. The Tenggerese, who like to gather in the pawon, are very strategic in carrying out education in the family because parents will be free to communicate with children in the Tenggerese tribal family. This teaching is done through various methods, including examples, traditional advice, and methods of attention or supervision. The pawon is so important and valuable as it becomes an effective place to internalize the values of multicultural education from an Islamic perspective which is carried out through those methods mentioned. These values include a) al-mushawarah (democracy), al-musawah (equality), al-‘adl (justice), habl min an-nas (humanity), al-ta’aruf (knowing each other), al-ta’awun (cooperation), al-salam (peace), al-tasamuh (tolerance), al-ukhuwwah (brotherhood). With these values, it is hoped that children will be ready to live in a multicultural society, especially in Tengger, where significant differences in religion and culture exist.